Statistical Success: Three-Year Analysis of Student Performance and Student Insights from a First-Year College Statistics Course - Harris, Jennifer D. (Advances in Social Sciences Research Journal, 2023)
This study included quantitative and qualitative analysis of three years of students in an introductory college-level statistics course. The quantitative analysis focused on what aspects might be relevant to student success. The instructor and the modality appear to be significantly related to student success. Somewhat surprisingly, fully onsite courses had a lower success rate than online or partially online courses. The qualitative analysis focused on the student comments on end of course surveys for the same three years. These comments were categorized based on topic and then rated from -3 reflecting a strong negative feeling, through to +3 indicating a strong positive feeling. These comments highlighted the importance students placed on live online lessons with the instructor. Students also appeared to take responsibility for their learning, noting the importance of their engagement to their success. This study provided unique insights to student success in an introductory college-level statistics course. Instructor and student engagement is key, along with opportunities for live connections.